Landscape change as an interface for different approaches in landscape research - Potthoff, Kerstin (ERDKUNDE, 2007)
Landscape is a topic of interest for many disciplines, and the importance of considering different approaches that may be complementary has been pointed out by several authors. However, interdisciplinary work applying both cultural and ecological approaches to landscape is challenging. One possible way to deal with these challenges is to study a common interest - an interface. The interface dealt with in this paper is landscape change. In the human-geographical and landscape-ecological literature, three broad perspectives on landscape change are identified. A first perspective deals with natural and human factors as causes of change. This perspective is mainly concerned with physical landscape changes. A second perspective concentrates on perception of, attitudes to, and meanings of landscape. The physical landscape plays a certain role, but more focus is placed on its perception. A third perspective focuses on the temporal and/or spatial dimensions of change. When applied to a Norwegian case study, the three perspectives on landscape change help to reveal the high complexity inherent in landscape change. Knowledge of this complexity can support conscious decisions about future development and a weighting of the consequences of different management alternatives.